Arabidopsis Group IIId ERF proteins positively regulate primary cell wall-type CESA genes - Saelim, Laddawan; Akiyoshi, Nobuhiro; Tan, Tian Tian; Ihara, Ayumi; Yamaguchi, Masatoshi; Hirano, Ko; Matsuoka, Makoto; Demura, Taku; Ohtani, Misato (Springer Verlag, 2019)
The cell wall determines morphology and the environmental responses of plant cells. The primary cell wall (PCW) is produced during cell division and expansion, determining the cell shape and volume. After cell expansion, specific types of plant cells produce a lignified wall, known as a secondary cell wall (SCW). We functionally analyzed Group IIId Arabidopsis AP2/EREBP genes, namely ERF34, ERF35, ERF38, and ERF39, which are homologs of a rice ERF gene previously proposed to be related to SCW biosynthesis. Expression analysis revealed that these four genes are expressed in regions related to cell division and/or cell differentiation in seedlings (i.e., shoot apical meristems, the primordia of leaves and lateral roots, trichomes, and central cylinder of primary roots) and flowers (i.e., vascular tissues of floral organs and replums and/or valve margins of pistils). Overexpression of ERF genes significantly upregulated PCW-type, but not SCW-type, CESA genes encoding cellulose synthase catalytic subunits in Arabidopsis seedlings. Transient co-expression reporter analysis indicated that ERF35, ERF38, and ERF39 possess transcriptional activator activity, and that ERF34, ERF35, ERF38, and ERF39 upregulated the promoter activity of CESA1, a PCW-type CESA gene, through the DRECRTCOREAT elements, the core cis-acting elements known to be recognized by AP2/ERF proteins. Together, our findings show that Group IIId ERF genes are positive transcriptional regulators of PCW-type CESA genes in Arabidopsis and are possibly involved in modulating cellulose biosynthesis in response to developmental requirements and environmental stimuli. © 2018, The Botanical Society of Japan and Springer Japan KK, part of Springer Nature.